The water-babies : a fairy tale for a land-baby - Kingsley, Charles, 1819-1875. (New York : Puffin, 1994)
The adventures of Tom, a sooty little chimney sweep with a great longing to be clean, who is stolen by fairies and turned into a water baby.
"Abridged.".
"Published in Puffin Books 1984"--T.p. verso.
8.3
5-8
Keywords: Chimney sweeps -- Juvenile fiction; Chimney sweeps -- Fiction; Fantasy; Chimney sweeps -- Fiction; Fantastic fiction